Socio-anthropological research: dialogical strategy for the construction of the preliminary diagnosis of school reality (Research, Society and Development, 2020)
This research aims to describe the stages of the construction process and development of Socio-anthropological Research. The socio-anthropological research is set up as a qualitative approach of investigative character for the knowledge of reality. It was carried out by members of the Institutional Program for Teaching Initiation Scholarship, a Natural Sciences subproject in a municipal public school in Uruguaiana, Rio Grande do Sul. The theoretical and methodological foundations used are based on the approximation with stages of Freire's Thematic Research, being semi-structured questionnaires the instruments of information production. The socio-anthropological research allowed to know specific characteristics of the investigated school community, such as issues related to economic, social, cultural and environmental aspects. As a result of the investigative process, a preliminary diagnosis of the reality was delivered to the school board, with the promise of considering the research in the revision of the school's Political Pedagogical Project, which may enable the construction of contextualized educational practices.